Submicroscopic infection of placenta by Plasmodium produces Th1/Th2 cytokine imbalance, inflammation and hypoxia in women from north-west Colombia (2014)
ABSTRACT: Background A large-scale study was set up in order to study the epidemiology, clinical aspects, and immunopathology of gestational and placental malaria in north-west Colombia. In this region, recent reports using a qPCR technique, confirmed frequencies of infection, by Plasmodium falciparum or Plasmodium vivax, up to 45%. Given the high rates of infection observed both in mother and placenta, a first exploratory study was proposed in order to characterize the effect on the inflammation status, tissue damage and hypoxia in Plasmodium spp. infected placentas. Methods A descriptive, prospective, cross-sectional design was applied to pregnant women with (PM+) and without (PM-) placental malaria. Messenger RNA expression of Fas, FasL; COX-1, COX-2, HIF, VEGF, and the cytokines IL-2, IL-4, IL-10, IFN-γ and TNF, were measured in peripheral and placental blood using a quantitative PCR. The percentage of apoptotic cells was determined with a TUNEL assay. Results In total 50 placentas were studied: 25 were positive for submicroscopic infection and 25 were negative for Plasmodium infection. Expression of IL-4 and IL-10 was observed high in placental tissue of PM+, while IL-2 was high in peripheral blood of the same group. Expression of TNF and IFNγ in peripheral blood of the PM + group was high. Similarly, the apoptotic index and Fas expression were significantly high in PM+. However, FasL expression was observed low in PM + compared to PM-. Inflammation markers (HIF, VEGF) and hypoxia markers (COX-1, COX-2) were high in the PM + group. Conclusion During placental malaria expression of some pro-inflammatory cytokines is up-regulated and markers of hypoxia and tissue damage are increased in cases of submicroscopic infection.